A proposito dell’infinito articolato nel Nuovo Testamento - Pierri, Rosario (Liber Annuus, 2009)
Abstract The attempt to systematically and coherently classify the uses of the article in the Greek language has long been an interesting field of research for many scholars. It is not always possible to give an unequivocal explaination as to why a given construct, found in similar contexts, sometimes can be found with the article and sometimes without. Grammarians and Exegetes have formulated varying interpretions of the function of the article, consequently leading to noteworthy differences at the level of interpretation. This article summarizes and discusses some of the fundamental aspects of the theory proposed by D. Burk on the use of articular infinitives, found in his monograph dedicated to this subject. One of the results of this present research is that the linguistic approach used by Burk while on the one hand, provides a comprehensive analyisis of the syntax of the use of the articular infinitive, on the other, does not propose a clear theory for a better understanding of articular infinitives in the New Testament as an alternative to the traditional grammar theory.